Faktor individu dalam prediksi diabetes mellitus tipe 2 di Salatiga Jawa Tengah - Priscila Evangelin Asa; Dibyo Pramono; Suryono Yudha Patria (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Individual factors as predictors of diabetes mellitus in SalatigaPurposeThe purpose of this study was to determine the relationship of the individual factors with the incidence of diabetes mellitus in Salatiga.MethodsThe research was a case control study conducted from April to June 2016 around the existing health centers in the Salatiga. The total sample was 156 respondents. Data analysis used McNemar’s Chi-square and multiple logistic regression conditional tests.ResultsThe variables associated with the incidence of diabetes mellitus was a family history of diabetes. People who have a family history of diabetes have a risk 41 times more likely to develop diabetes mellitus compared with people who do not have a family history of diabetes mellitus in Salatiga.ConclusionThis study concluded that the incidence of diabetes mellitus is affected by family history. Primary health care is expected to cooperate with health office to conduct prevention efforts such as activities that encourage physical activity.